True Betrayals - Roberts, Nora (New York : Jove, 2021)
A romantic thriller set in the world of horse racing. It begins when Kelsey Byden discovers her mother--supposedly dead for 20 years--is in jail for killing her lover. The mother owns a racing stable in Virginia whose neighbor is handsome Gabe Slater. Kelsey and Gabes meeting leads to rivalry, love and murder.
"G.P. Putnams Sons hardcover edition / June 1995. First Jove mass-market edition / May 1996." -- Title page verso.
Keywords: Mothers and daughters -- Fiction; Horse racing -- Fiction; Man-woman relationships -- Fiction; Family secrets -- Fiction; Murder -- Fiction; Virginia -- Fiction; Romantic suspense fiction; Domestic fiction